Muscle-Derived Cells for Treatment of Iatrogenic Sphincter Damage and Urinary Incontinence in Men - H. Gerullis; C. Eimer; E. Georgas; M. Homburger; A. G. El-Baz; M. Wishahi; M. Borós; T. H. Ecke; T. Otto (The Scientific World Journal)
Introduction. Aim of this study was to assess the safety and efficacy of injection of autologous muscle-derived cells into the urinary sphincter for treatment of postprostatectomy urinary incontinence in men and to characterize the injected cells prior to transplantation. Methods. 222 male patients with stress urinary incontinence and sphincter damage after uroloical procedures were treated with transurethral injection of autologous muscle-derived cells. The transplanted cells were investigated after cultivation and prior to application by immunocytochemistry using different markers of myogenic differentiation. Feasibility and functionality assessment was achieved with a follow-up of at least 12 months. Results. Follow-up was at least 12 months. Of the 222 treated patients, 120 responded to therapy of whom 26 patients (12%) were continent, and 94 patients (42%) showed improvement. In 102 (46%) patients, the therapy was ineffective. Clinical improvement was observed on average 4.7 months after transplantation and continued in all improved patients. The cells injected into the sphincter were at least ~50% of myogenic origin and representative for early stages of muscle cell differentiation. Conclusions. Transurethral injection of muscle-derived cells into the damaged urethral sphincter of male patients is a safe procedure. Transplanted cells represent different phases of myogenic differentiation.